Mobile Broadband Module Simulation Framework - Simplifying Client Driver Development through Test Environment Control - Runemalm, David; Sandell, Fredrik (My University, 2012)
Software drivers are typically hard to debug since their operation is closely linked to the functionality of the hardware for which they are developed. The problems with driver debugging is especially complicated if the hardware device has got interdependencies on complicated external systems, as is the case with 3G modems. The purpose of this thesis is to develop a 3G modem simulator framework that can be used to control the environment in which 3G modem drivers are developed. Using a simulator to control a development environment is not a new approach. However, up to this point a modem simulator has not been used during 3G modem driver development. The modem simulator described in this thesis is implemented on a separate piece of hardware which ensures that it can be used with any host system. The simulator is highly configurable and can be used to induce 3G modem failures to test edge cases and stress test the driver software. Tests have been performed which shows that the system is indeed capable of simulating a 3G modem when attached to different host systems. The mobile communication industry is constantly evolving, therefore future development of the simulator system is proposed that would increase the capabilities of the system and keep it up to date and ready for the next generation of modems.
Keywords: Datavetenskap (datalogi); Computer Science